The effect of electron correlation on the adsorption of hydrogen fluoride and water on magnesium fluoride surfaces. Issue 28 (28th July 2015) - Kanaki, Elisavet; Sansone, Giuseppe; Maschio, Lorenzo; Paulus, Beate
<x xml:space="preserve">Abstract</x> Periodic DFT and local MP2 calculations elucidate the role of electron correlation in the adsorption of H2O and HF on MgF2 surfaces.